Whole-genome expression profiling of Xylella fastidiosa in response to growth on glucose - Pashalidis, S.; Moreira, L. M.; Zaini, P. A.; Campanharo, J. C.; Alves, LMC; Ciapina, L. P.; Vencio, RZN; Lemos, EGM; Da Silva, A. M.; da Silva, ACR (Mary Ann Liebert, Inc., 2005)
Xylella fastidiosa is the etiologic agent of diseases in a wide range of economically important crops including citrus variegated chlorosis, a major threat to the Brazilian citrus industry. The genomes of several strains of this phytopathogen have been completely sequenced enabling large-scale functional studies. In this work we used whole-genome DNA microarrays to investigate the transcription profile of X. fastidiosa grown in defined media with different glucose concentrations. Our analysis revealed that while transcripts related to fastidian gum production were unaffected, colicin-V-like and fimbria precursors were induced in high glucose medium. Based on these results, we suggest a model for colicin-defense mechanism in X. fastidiosa.